Production of designer egg: Effects of various n-3 lipid sources on fatty acids composition and sensory characteristics of chicken egg - VALAVAN, S EZHIL; MOHAN, B; SELVARAJ, P; RAVI, R; MANI, K; EDWIN, S C; BHARATHIDHASAN, A (The Indian Journal of Animal Sciences, 2013)
Layer biological experiment was conducted to study the effect of various n-3 lipid sources such as fish, linseed and rapeseed oils to enrich n-3 or omega -3-fatty acids in chicken egg from 20–70 weeks of age. The supplementation of n-3 lipid sources in layer ration significantly increase linolenic acid, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), total n-3 fatty acids, total n-6 fatty acids and total n-3/n-6 fatty acids ratio of egg yolk, and a significant reduction in palmitic and stearic acid concentrations. The total unsaturated fatty acids concentration in egg yolk showed an increase in all the treated groups due to incorporation of various n-3 lipid sources in feed. The inclusion of n-3 lipid sources (at 1, 2 and 3% levels) independently and simultaneously in feed had no adverse effect on sensory quality of egg. Feeding layers with 3% fish oil showed significant increase in EPA, DHA and total n3 fatty acids in egg yolk.